Linking branding strategy to ownership structure, financial performance and stability: case of French wine cooperatives. (2019) - Challita, Sandra; Aurier, Philippe; Sentis, Patrick
This research explores the relationship between the branding and financial performance of a firm while taking into account its ownership structure. Using decisional theory, we apply a normative approach to better explain the incentives and constraints of branding in two types of firms: cooperatives and investor-owned firms (IOFs). We then perform a quantitative analysis using a survey of 207 French firms in the wine sector and financial information data. We show that cooperatives are more constrained to private branding. As a consequence, they invest more in labelling, whereas IOFs are more likely to invest in private branding. Additionally, we find that branded (private and labelling) firms have poorer financial and commercial performance, as measured by return on assets and return on sales ratios, respectively. Finally, we find that the main factor contributing to the stability of financial performance is a cooperative ownership structure rather than the branding strategy.